2008
DOI: 10.1063/1.2907722
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy electron diffraction and induced damage in hydrated DNA

Abstract: Elastic scattering of 5-30 eV electrons within the B-DNA 5'-CCGGCGCCGG-3' and A-DNA 5'-CGCGAATTCGCG-3' DNA sequences is calculated using the separable representation of a free-space electron propagator and a curved wave multiple scattering formalism. The disorder brought about by the surrounding water and helical base stacking leads to a featureless amplitude buildup of elastically scattered electrons on the sugar and phosphate groups for all energies between 5 and 30 eV. However, some constructive interferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 50 publications
2
49
0
Order By: Relevance
“…18 Other experiments with electrons were performed with a direct beam source. 10,34,30,33 From the same experiment, Cai et al 29 obtained a ratio of 11.4 for 1.5 keV photons in excellent agreement with the calculation of Fulford et al 35 The results of Le Sech et al 36 were recorded above (SSB/DSB=11) and below (SSB/DSB=13) the energy of LIII inner shell absorption of Pt, which was attached to the DNA.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…18 Other experiments with electrons were performed with a direct beam source. 10,34,30,33 From the same experiment, Cai et al 29 obtained a ratio of 11.4 for 1.5 keV photons in excellent agreement with the calculation of Fulford et al 35 The results of Le Sech et al 36 were recorded above (SSB/DSB=11) and below (SSB/DSB=13) the energy of LIII inner shell absorption of Pt, which was attached to the DNA.…”
Section: Resultssupporting
confidence: 73%
“…As suggested by Orlando et al, 34 two successive breaks induced by a single LEE could provide an explanation. The cross-section for a 10 eV electron to break one bond in the backbone of a DNA molecule made of 3197 base pairs is about 10 −15 cm 2 .…”
Section: B Damage Induced By 10 Ev Electronsmentioning
confidence: 94%
“…Complexes of H 2 O with DNA have previously been identified via the appearance of new structures in the ESD yield of H − from oligonucleotide films when they are hydrated at cryogenic temperatures. 11 Later theoretical and experimental work 12 suggests that the presence of structural water in the major grooves of DNA strongly perturbs electron diffraction within DNA and that H 2 O:DNA states involving core-excited resonances based on those of H 2 O likely contribute to LEE induced strand break damage. 12 If indeed the 18 OH − signal arises from 18 O 2 strongly bound physically or chemically to DNA, it might be expected to exhibit a quite different behaviour as a function of the sample temperature than that of the 18 O − signal.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been shown that organic ions 9 and proteins 10 protect DNA against LEE-induced damage and that the presence of water around DNA modifies the TNI manifold and corresponding decay channels. 11,12 O 2 is another molecule present with DNA in the cell nucleus and is known as an efficient radiosensitizer. Studies on the radiosensitization of biological damage by molecular oxygen in living cells began about a century ago and have remained one of the most significant subjects in radiobiology.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering work in the year 2000 from the group of Boudaïffa [35] there have been several attempts to repeat and extend these studies but with varying degrees of success and results have shown significant differences [75][76][77]. These differences are mainly due to the difficulty that AMP groups have in preparing DNA films for irradiation.…”
Section: Preparation Of Dna Films For Vacuum Studies Of Dna Damagementioning
confidence: 99%